Sterols from Vietnamese marine sponge Tethya aurantium - Cuc, Nguyen Thi; Thuy Hang, Dan Thi; Tai, Bui Huu; Nhiem, Nguyen Xuan; Anh Tuan, Hoang Le; Yen, Pham Hai; Doan, Vu Van; Minh, Chau Van; Kiem, Phan Van (Vietnam Journal of Chemistry, 2015)
Chemical investigation on Vietnamese marine sponge Tethya aurantium resulted in the isolation of five sterols, including 5R,6R-epoxy-24R*-ethylcholesta-8-en-3β,7α-diol (1), 24-methylenecholesta-5-en-3β-ol (2), 24-norcholesta-5,22E-dien-3β-ol (3), 5α,8α-epidioxy-24R*-ethylcholesta-6-en-3β-ol (4), and 5α,8α-epidioxy-24S-methylcholesta-6,22E-dien-3β-ol (5). Their chemical structures were successfully determined using NMR and ESI-MS analysis as well as in comparison with the reported literatures. Stereochemistry of C-24 in the side chain of isolated sterols was also discussed. This is the first study on chemical constituents from the sponge T. aurantium. Keywords. Steroid, Tethya aurantium, Vietnamese sponge.